PENGARUH SELF EFFICACY, LINGKUNGAN KELUARGA DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI UNISDA LAMONGAN - Siti Shoimah (J-MACC, 2019)
The background of this research is intellectual unemployment which is increasing due to lack of awareness among the younger generation to create their own jobs. The purpose of this study was to analyze the influence of self efficacy, family environment and entrepreneurship education to student interest in entrepreneurship. The sampling technique uses purposive sampling. Respondents in this study amounted to 90 respondents. The independent variables in this study is self efficacy, family environment and entrepreneurship education. Dependent variables in this study is student interest in entrepreneurship. This study uses multiple linear regression analysis using SPSS version 22.0. The results of this study indicate that all the independent variables in this study have an influence on the dependent variable, both partially and simultaneously, while the social media variables, motivation and environment that influence the interest in entrepreneurship have a mediating relationship partially or simultaneously. Keywords: , Family Environment, Entrepreneurship education and Student Interest in Entrepreneurship